Fermenting milk to reduce acid sensitive bacteria - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Evaluated in Ethiopia and Kenya: effective for aflatoxin & Staph aureus REMOVE. Upon more consideration, we elect not to count this as an innovation.